Influence of Particle Size Distribution on the Physical Characteristics of Pore-Filling Hydrate-Bearing Sediment - Peng Wu; Shenghua Yang; Le Wang; Xiangge Song; Yanghui Li (Geofluids)
Nature gas hydrates (NGHs) are regarded as a potential alternative energy source due to their huge reserves and wide distribution. According to the geophysical surveys, the pore-filling hydrates occupy a large proportion of the global hydrate reserves, especially for the marine regions. Therefore, with a novel pore-scale 3D morphological modeling algorithm, this study systematically studied the effect of the particle size on the physical characteristics of the pore-filling hydrate-bearing sediment (HBS). The pore system evaluations and permeability simulations were performed by utilizing pore network modeling (PNM), and the thermal and electrical simulations were conducted by utilizing a finite volume method (FVM). The results show that for the HBS with smaller particle size, the average radius of the pores and throats would also be reduced, and the fractal dimension of the pore system would be increased. In addition, with the increasing hydrate saturation, the fractal dimension of the pore system will increase firstly and then decrease. And these parameter evolutions could impact the physical properties correspondingly; specifically, the decreasing particle size in the HBS would reduce the permeability and electrical conductivity of HBS and enhance the apparent thermal conductivity of HBS.